PENGARUH PERMAINAN MAZE ANGKA TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA ANAK USIA 4-5 TAHUN - Siti Rohmah; Winarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the effectiveness of using the educational game Maze Angka (APE Maze Angka) in enhancing critical thinking skills among children aged 4-5 years at TK Indriyasan, Sleman. The underlying issue of this research is the importance of teaching methods that support critical thinking skills in early childhood education, particularly in addressing the challenges of 21st-century education. This research employed a quantitative approach with a one-group pretest-posttest design. The study sample consisted of 15 children selected purposively. Data were analyzed using validity, reliability, normality, homogeneity tests, and t-tests with the assistance of SPSS 25 software. The findings revealed a significant improvement in children's critical thinking skills after the intervention using Maze Angka, with the average pretest score increasing from 26.0 to 33.85 in the posttest. The instruments used were proven valid (r-calculated > r-table = 0.444) and reliable (Cronbach’s Alpha = 0.831). The research data also met statistical assumptions, with normality and homogeneity tests showing significance values > 0.05. The t-test indicated a significant difference between pretest and posttest scores (t = -16.081, p = 0.000). These findings demonstrate that Maze Angka is an effective learning strategy to support cognitive development in early childhood. The game stimulates critical thinking skills through exploratory activities and problem-solving. Therefore, Maze Angka is recommended as an innovative learning medium for early childhood education.